Makna dalam Merawat: Studi Kualitatif Tulisan Benefit-Finding pada Family Caregiver Orang Dengan Demensia (ODD) - Febby Rosa Annisafitrie; Zainal Abidin; Kustimah Kustimah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Caregivers of people with dementia (ODD) are often associated with heavy emotional, physical, and social burdens. However, several studies have shown that caregivers can also find positive meaning in the experience through the process of seeking meaning. This study aims to explore the positive aspects experienced by caregivers and the meanings formed during the caregiving process of individuals with dementia (ODD) through qualitative methods using a descriptive phenomenological approach. Eleven participants participated in a seven-day writing intervention involving seeking meaning. Data were analyzed using reflective thematic analysis. The results identified six main themes: (1) personal growth, (2) spiritual growth, (3) strengthening relationships, (4) appreciation for life, (5) meaning in the caregiving process, and (6) increased competence and mastery of caregiving skills. These findings suggest that reflective writing can facilitate the process of constructing positive meaning in the caregiving experience. Although some participants indicated limitations in writing, the writing intervention, based on seeking meaning, still holds potential as a simple, cost-effective, and flexible approach that can be delivered from anywhere. However, its comfort can be enhanced through combination with individual or group mentoring, tailored to the preferences of families caring for individuals with ODD.